(untitled) (Teacher’s World: Journal of Education and Research, 2024)
The National Curriculum of Bangladesh (2012) recommends student-centric IBT (IBT) learning activities in the science classroom. However, teaching science in Bangladesh is hardly follows the instructions of curriculum, and most teachers are found not to place adequate emphasis on involving the students in the inquiry process. A possible reason might be science teachers’ belief. The focus of the research questions is to find out firstly, the beliefs of both urban and rural sixth grade science teachers and secondly, the differences between genders and lastly to explore the challenges of IBT. Thereby, a sequential explanatory mixed method was adopted for this study. The participating teachers were from both rural and urban areas. An interview was taken to support statistical and quantitative data for an in-depth explanation. The result revealed that teachers from both urban and rural areas have positive beliefs towards inquiry, and there is no significant difference between urban-rural and male-female teachers. In the case of urban teachers, the challenges were time and classroom management, but not for rural teachers. This study recommends that stakeholders use the inquiry instruction, reshape the training, and provide the teachers with the necessary opportunities for professional development programs in an effective way. Teacher’s World: Journal of Education and Research, 49 (2),135-149